Functional imaging research in schizophrenia - Tost, Heike; Ende, Gabriele; Ruf, Matthias; Henn, Fritz A.; Meyer-Lindenberg, Andreas (International review of neurobiology, 2005)
In the preceding decade, functional neuroimaging has emerged as a pivotal tool for psychiatric research. Techniques such as magnetic resonance imaging (MRI) and positron emission tomography (PET) help bridge the gap between genetic and molecular mechanisms and psychological and behavioral phenomena by characterizing brain dysfunction underlying psychiatric disorders on the neural systems level. This has been of particular relevance for schizophrenia research. This chapter reviews important fMRI studies in neurocognitive domains relevant for schizophrenia, such as motor, visual, auditory, attentional, and working memory function, as well as advances in the visualization of medication effects and the functional characterization of susceptibility genes.